Answered by AI, Verified by Human Experts

The solution to theequation5x - 3(4x - 8) = -11 is x = 5.The given equation is 5x - 3(4x - 8) = -11.First,distributethe -3 to the terms inside the parentheses:5x - 3(4x - 8) = -115x - 12x + 24 = -11Combining like terms:-7x + 24 = -11Next, isolate thevariablex by moving the constant term to the other side of the equation:-7x = -11 - 24-7x = -35Finally, solve for x bydividingboth sides of the equation by -7:x = (-35) / (-7)x = 5Therefore, thesolutionto the equation is x = 5.To learn more onEquation:brainly.com/question/10413253#SPJ6...

Unlock full access for 72 hours, watch your grades skyrocket.

For just $0.99 cents, get access to the powerful quizwhiz chrome extension that automatically solves your homework using AI. Subscription renews at $5.99/week.